Independent Association of Serum Fibroblast Growth Factor 21 Levels With Impaired Liver Enzymes in Hyperthyroid Patients - Xiao, Fangsen; Zeng, Jinyang; Huang, Peiying; Yan, Bing; Zeng, Xin; Liu, Changqin; Shi, Xiulin; Wang, Liying; Song, Haiqu; Lin, Mingzhu; Yang, Shuyu; Li, Zhibin; et al. (Frontiers in Endocrinology, 2019)
Fibroblast growth factor 21 (FGF21) is identified as a potential biomarker for liver diseases. However, information is limited regarding serum FGF21 and impaired liver function in hyperthyroidism. We aim to determine the potential association of serum FGF21 levels with impaired liver enzymes in hyperthyroid patients. In this case-control study, 105 normal subjects and 122 overt hyperthyroid patients were included. Among them, 41 hyperthyroid patients who obtained euthyroid status after thionamide treatment received second visit. Serum FGF21 levels were determined using the ELISA method. Compared to the normal subjects, patients with hyperthyroidism had significantly elevated serum liver enzymes, including alanine transaminase (ALT) (p<0.001), aspartate aminotransferase (AST) (p<0.001) levels, as well as FGF21 levels (p<0.001). Further analysis showed serum FGF21(p<0.05), as well as thyroid hormone free T3(p<0.05), free T4(p<0.05) levels were higher in hyperthyroid patients with impaired liver enzymes than in those with normal liver enzymes. After reversal of hyperthyroid state, elevated serum FGF21 levels in hyperthyroid patients declined significantly (p<0.001), with a concomitant decrease in serum ALT (p<0.001), AST (p<0.001) levels. Correlation analysis showed close correlation between FGF21 and ALT (p=0.002), AST (p=0.012), free T3 (p<0.001), free T4 (p<0.001). Further logistic regression analysis revealed FGF21 is significantly associated with elevated ALT [Odds Ratio, OR 1.79, (95% confidence interval, CI), (1.30-2.47), P<0.001], AST [1.59(1.07-2.34), p=0.020]. After adjustment of potential confounders, the association between FGF21 and elevated ALT remained significant [1.42(1.01-1.99), p=0.043]. In conclusion, serum FGF21 is independently associated with impaired liver enzymes in hyperthyroid patients.